2022
DOI: 10.1007/s00404-022-06888-4
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean scar pregnancy: is there a light in the end of the tunnel?

Abstract: Purpose: to summarize and present a single tertiary center's 25 years of experience managing patients with caesarean scar pregnancies and their long term reproductive and obstetric outcomes.Methods: A 25-year retrospective study included women diagnosed with CSP from 1996 to 2020 in one tertiary center. Data were retrieved from the medical records and through a telephone interview. Diagnosis was made by sonography and color Doppler. Treatments included methotrexate, suction curettage, hysteroscopy, embolizatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Using the classification proposed by the CSP taskforce 23 , we found that all women with a history of CSP in which the gestational sac protruded over the serosal line in the midsagittal plane presented with a uterine niche on SCSH and were more likely to have greater niche length and depth, and smaller RMT than those who had the largest part of the gestational sac protruding towards the uterine cavity or embedded in the myometrium. Overall recurrence rate in women with previous CSP can vary across studies (9-25%) [24][25][26][27] . Timor-Tritsch et al 28 found a higher rate of 34.3% and Ben Nagi et al 29 argued that a very large niche could be the cause of CSP after CD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the classification proposed by the CSP taskforce 23 , we found that all women with a history of CSP in which the gestational sac protruded over the serosal line in the midsagittal plane presented with a uterine niche on SCSH and were more likely to have greater niche length and depth, and smaller RMT than those who had the largest part of the gestational sac protruding towards the uterine cavity or embedded in the myometrium. Overall recurrence rate in women with previous CSP can vary across studies (9-25%) [24][25][26][27] . Timor-Tritsch et al 28 found a higher rate of 34.3% and Ben Nagi et al 29 argued that a very large niche could be the cause of CSP after CD.…”
Section: Discussionmentioning
confidence: 99%
“…Overall recurrence rate in women with previous CSP can vary across studies (9–25%) 24–27 . Timor‐Tritsch et al 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Hence our department's current policy is to recommend termination of these pregnancy as soon as the diagnosis is made. 26 The Society for Maternal-Fetal Medicine (SMFM) recently recommended pharmacological treatment by local or intragestational injection of MTX with or without accompanying systemic MTX for those women who are eligible. 27 Systemic MTX alone is discouraged, given the higher risks of complications.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our experience, 2,3 the prognosis for an uneventful term pregnancy remains extremely poor. Hence our department's current policy is to recommend termination of these pregnancy as soon as the diagnosis is made 26 …”
Section: Discussionmentioning
confidence: 99%